Factors influencing on nutrient recycling in permanent grasslands and development of their modeling - Crespo, Gustavo (Cuban Journal of Agricultural Science, 2016)
This review examines studies on factors influencing on nutrient recycling in permanent grasslands: soil organisms, litter, radicular systems of grasses and animal excretions. It also analyzes the evolution of researches aimed to modeling the recycling process. Some considerations and recommendations are also stated for further researches on this subject. Key words: permanent grasslands, nutrient recycling, modeling